Problems of bread making - Alexander, Lizzie Bea (My University, 1907)
Introduction: This the most universally used of all foods that is made. All men, in all conditions, in all countries, use bread in some form. Wheat bread is the commonest form, limiting the word bread to that which is leavened by yeast. For years, wheat and other cereals, were crushed between rollers or stones. The flavor of bread, made by the use of yeast, is very pleasant and complex, and hence, never produces satiety. This is one of the important reasons why bread can be and is used universally. There are no specific rules that can be laid down for making bread. So much depends upon quality of yeast and flour, temperature, atmospheric changes, and other conditions which bring about variations in regard to fermentation of the bread. Close observation and practice well supply the lack of unvarying rules in bread making. Bread is an article of diet which contains all the foods necessary for…
Citation: Alexander, Lizzie Bea. Problems of bread making. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Bread; Bread Making; Composition of Bread; Theses; Manuscripts (documents)